?OLLOIDAL-CHEMICAL CHARACTERISTICS OF FLOTATION REGULATORS FOR DESLIMING SYLVINITE ORES - BukhorovSh.B., KholmurodovSh.?., Abdikamalova?.B., EshmetovI.D., IrgashevichKh.?. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The research results aimed at obtaining new import-substituting sludge collectors (SC) for flotation sylvinite ores desliming and studying their colloidal-chemical and technological characteristics are presented. The foaming properties study of the synthesized surfactants and the analysis of the formed foams stability degree showed their relatively high stability at the moment of their inception. It turned out that with an increase in the surfactants foaming properties, their stability also changes. Foams formed by the TIAB reagent are relatively the most stable, and those formed by EAF are relatively least stable; foams formed by other blowing agents occupy an intermediate position in this characteristic.